Characteristics and tanning potential of Hagenia abyssinica tannin extracts and its possible use in clean leather production. Issue 1 (1st January 2021) - John Unango, Franco; Duraisamy, Ramesh; Ramasamy, Karthikeyan M.; Birhanu, Tewodros
Abstract: Hagenia abyssinica, a tannin material, was employed for tanning the sheepskins into crust leathers and then compared its performance with the leather that was tanned with commercial mimosa. Characterizations of H. abyssinica extract revealed that it possesses condensed tannin having a pH: 4.7. Tannin, non-tannin, and tannin strength were found to be 15.49%, 7.52%, and 2.06% respectively. Fourier transforms Infrared and UV–Visible spectroscopic studies were also carried out to find the structural characteristics of the H. Abyssinica tannins. The results of the physicomechanical characterization of crust leathers showed that the tensile strength of the sample was ranged from 10.2 to 11.9 N/mm 2, but the control mimosa tanned leather was found to be 19.8–19.9 N/mm 2 . Elongation at break was 45.7–45.8% against control (36.7–37.5%). Tear strength was found as 26.9–27.3 N/mm 2 (expt.) and 26.9–27.8 N/mm 2 (control). The chemical properties of prepared scab leathers were tested and the obtained data met the desires. In addition, H. Abyssinica tanned leather exhibited the highest shrinkage temperature of about 78.5°C. Analyses of organoleptic properties showed that the H. Abyssinica crust leathers were much better than mimosa-based crust leather. The effluence masses of tanning liquors existed also assessed and the findings mostly demonstrated that there was a statistically significant difference (with p-values: 0.000) except total suspended solid (p-value: 0.059) and BOD (p-value: 0.099) between the control and experiment liquors within the allowable limit. Thus, this study exhibited that H. Abyssinica tanning liquor does not influence the pollution load into the aquatic environment and soil.